Answer:
x = -2
y = -1
(-2, -1)
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
- Equality Properties
<u>Algebra I</u>
- Solving systems of equations using substitution/elimination
- Solving systems of equations by graphing
Step-by-step explanation:
<u>Step 1: Define systems</u>
y = x + 1
3x + 3y = -9
<u>Step 2: Solve for </u><em><u>x</u></em>
<em>Substitution</em>
- Substitute in <em>y</em>: 3x + 3(x + 1) = -9
- Distribute 3: 3x + 3x + 3 = -9
- Combine like terms: 6x + 3 = -9
- Isolate <em>x</em> term: 6x = -12
- Isolate <em>x</em>: x = -2
<u>Step 3: Solve for </u><em><u>y</u></em>
- Define original equation: y = x + 1
- Substitute in <em>x</em>: y = -2 + 1
- Add: y = -1
<u>Step 4: Graph systems</u>
<em>Check the solution set.</em>
Lateral Surface Area of a square pyramid (4 isosceles triangles): For the isosceles triangle Area = (1/2)Base x Height. Our base is side length a and for this calculation our height for the triangle is slant height s. With 4 sides we need to multiply by 4. (hope this will help)
Well we can put that word problem into a equation so, 8+x/4=5. Now what I would do is move the 8 to the other side, and since it moved to the other side it becomes a -8 so now we have x/4 = -3. Now I would multiply both side by 4 to get x = -12
Answer= X = -12
Answer:
x=6
Step-by-step explanation:
Create equivalent expressions in the equation that all have equal bases then solve for X.
Hope this helped have a good one.